Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.22454/fammed.2019.270753
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Medical Student Burnout

Abstract: Background and Objectives: There is a paucity of longitudinal data documenting the temporal development of distress and burnout during medical school. The aim of this study was to examine trends and identify stressors associated with medical student distress over 4 years of medical education. Methods: Medical students from the class of 2016 at a Liaison Committee on Medical Education-accredited medical school completed surveys nine times from orientation through after the residency match. Surveys included demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 8 publications
3
39
1
Order By: Relevance
“…Additionally, the rate of burnout increased until the M3 year and then sharply decreasing during the M4 year. These ndings are similar to previous studies looking at the association between year in medical school and perceived burnout (13,31). We hypothesize that this association for second-year medical students is related to their preparation for the USMLE Step 1 Board Exam.…”
Section: Factors To Predict Burnout In Medical Studentssupporting
confidence: 90%
“…Additionally, the rate of burnout increased until the M3 year and then sharply decreasing during the M4 year. These ndings are similar to previous studies looking at the association between year in medical school and perceived burnout (13,31). We hypothesize that this association for second-year medical students is related to their preparation for the USMLE Step 1 Board Exam.…”
Section: Factors To Predict Burnout In Medical Studentssupporting
confidence: 90%
“…Burnout is more common amongst medical professionals than other workers and college graduates [2,3]. Burnout has been shown to increase during medical school and can persist in residents through training [4,5]. Multiple studies have demonstrated that patient care [1,6] and self-reported medical errors [7] can be negatively impacted by burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Also health professions students are at high risk of burnout. Indeed, a study conducted on a large sample of American medical students showed an increase of distress from 2% to 12% and burnout from 17% to 38% from matriculation through after the residency match, demonstrating the high risk of developing burnout during medical school [15].…”
Section: Introductionmentioning
confidence: 99%